Algorytmizacja przestrzeni internetowej - Szews, Przemysław (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2015)
The article tackles the problem of the existence of algorithms in selected services and the Internet websites. The interfacing of media is the starting point for this discourse, aimed at presenting the processes of automatisation in information distribution, the individualisation of messages, and profiling in websites. The threats resulting from dynamically developing enterprises aimed at providing the website user with artificial intelligence – in terms of both social networks and mobile applications – are explicated in detail. The examples presented in the article refer to Internet recommendation systems, e-mail applications, voice assistants, and mechanisms responsible for the functioning of social networks. Speculations on the algorithms omnipresent on the net lead us to reflect on how the journalist’s profession will be redefined in the future, since it seems that the role of the journalist will be to moderate discussion and select the themes to be discussed; it is quite likely, though, that the themes selected will be compiled by specialised software.